Odoo 15 Development Essentials - Fifth Edition Enhance Your Odoo Development Skills to Create Powerful Business Applications - Reis, Daniel (Packt Publishing, Limited, 2022)
Become a proficient Odoo developer and increase your productivity while building Odoo business applications Key Features Set up the Odoo development environment and learn how to test and debug your code Use the ORM framework to work with data and implement business logic supporting business rules Design user interfaces, web pages, and business reports using the Odoo framework's web components Book Description Odoo is fast becoming the reference open source platform for business applications thanks to the fact that it provides the infrastructure needed for developers to deliver software solutions for any business process quickly. Odoo's layered module approach makes it particularly effective for combining and extending features. This updated fifth edition is a tutorial-style introduction to essential Odoo development topics. The book starts by covering the development essentials for building business applications and takes you through Odoo installation and configuration, gradually transitioning from having no specific knowledge of Odoo to being ready for application development. You'll then learn how to develop your first Odoo application, while covering topics such as models and views. Later chapters will get you up to speed with using server APIs to add business logic, helping you lay a solid foundation for advanced topics. As you progress, you'll get equipped to build and customize your applications and explore the new features available in Odoo 12 and beyond, such as in-memory ORM and computed writable fields. Finally, you'll gain insights into building business logic and using the Odoo API to integrate with various applications. By the end of this book, you'll be able to build business apps from scratch using the latest version of Odoo. What you will learn Install Odoo from source and organize the development environment Create your first Odoo app from scratch Understand the application components available in Odoo Structure the application's data model using ORM features Use the ORM API to implement the business logic layer Design a graphical user interface (GUI) for the web client and website Use the Odoo External API to interface with external systems Deploy and maintain your application in production environments Who this book is for This book is for developers who want to learn Odoo application development and quickly become productive while creating business applications. Teachers, trainers, and Odoo team managers will also find the book useful for helping their students or trainees to learn Odoo development skills. Basic knowledge of Python programming is required to get started with the book.
Print version record
Keywords: Application software -- Development; Computing platforms; Logiciels d'application; Développement; Plateformes (Informatique); COMPUTERS; Enterprise Applications; General; COMPUTERS; Software Development & Engineering; General; COMPUTERS; Programming Languages; Python; Application software; Development